INTENSITAS PENYAKIT ANTRAKNOSA CABAI PADA PERLAKUAN PGPR DAN POTENSI SENSOR TERMAL UNTUK DETEKSI DINI - Amalia, Khafidah; Ramdan, Evan Purnama; Arti, Inti Mulyo (Universitas Gunadarma, 2024)
Chilli peppers are easily infected with anthracnose disease caused by Colletotrichum gloeosporioides. Early detection, such as temperature changes with thermal sensors before visual symptoms appear, can prevent developing more severe diseases. This study aims to evaluate the potential of anthracnose detection using thermal sensors in chilli and the intensity of anthracnose disease in applying Plant Growth Promoting Rhizobacteria (PGPR). This study used a completely randomized complete group design (RKLT). PGPR was applied twice at the seedling preparation stage and at the plant age 30 days after planting (HST). Seeds that are ready to be sown are soaked first with 3 dose treatments, namely; without pgpr as control (P0), PGPR 25 g/5 L sterile distilled water (P1) and 50 g/5 L sterile distilled water (P2). Apart from that, PGPR application was also carried out on plants aged 30 HST with no PGPR as a control (P0), a dose of 100 mL PGPR/plant (P1), 200 mL PGPR/plant (P2). The results showed that the thermal sensor has the potential as an early detection method of anthracnose disease, as seen from the difference in the temperature of chilli fruit pre-inoculation with post-inoculation by 2 - 3ºC. In addition, PGPR treatment was able to suppress anthracnose disease with the lowest disease incidence of 19,33% (P1), disease severity of 16,56% (P2) and AUDPC of 49,38 units (P1).